Manajemen Strategi Dinas Kebudayaan Kepemudaan dan Olahraga serta Pariwisata Guna Pengembangan Kawasan Wisata Pecinan Kya – Kya Kota Surabaya - Aliy, Adhim Lathif; M, Meirinawati; Fanida, Eva Hany; Oktariyanda, Trenda Aktiva (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Surabaya City has various heritage tourism potentials that can be developed as leading tourist attractions, one of which is the Kya–Kya Kembang Jepun Chinatown Tourism Area. This area is a cultural and historical tourism destination with high historical, social, and cultural value, making it highly potential for sustainable development. The management of this tourism area requires the implementation of appropriate strategic management to enhance tourist attractiveness, increase the number of visitors, and provide positive contributions to the local economy and the preservation of cultural values. This study aims to examine and analyze the strategic management of the development of the Kya–Kya Chinatown Tourism Area implemented by the Department of Culture, Youth and Sports, and Tourism of Surabaya City. This research employs a descriptive method with a qualitative approach. Data collection techniques include field observations, in-depth interviews, and documentation involving the Department of Culture and Tourism, tourism area business actors, and visiting tourists. Data analysis was conducted using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The results indicate that the development strategy of the Kya–Kya Chinatown Tourism Area has referred to four tourism development indicators in accordance with the Regulation of the Minister of Tourism and Creative Economy Number 12 of 2020, namely accessibility, amenities, attractions, and promotion.